Enabling Retention of Rural Youth in Farming through Capacity Building – A Case Study - B. L. Dhaka and K. Chayal, (Indian Journal of Extension Education, 2014)
Youth contributes more than 40 per cent of Indina rural populatin. Due to their limited access to education and skillstraining, rural youth are often very low-skilled, unemployed and insecure. Youth living in rural areas do not have enoughincentives, profitable economic opportunities and attractive environments in which to live and work. Investing in youngpeople living in rural areas is key to enhancing agricultural productivity, boosting rural economies, and reducing rural-tourban migration. Realizing the potentiality of agriculture to significantly reduce poverty, enhance economic growth andentrench economic stability, the rural youth were equipped with necessary skills required to run dairy farm successfullythrough capacity building activities. The present paper is based on findings of a case study. A case study of a successfuldairy entrepreneur in Bundi district of Rajasthan state was conducted to analyse the effectiveness of capacity buildingstrategy to retain rural youth in farming. It was observed that capacity building approach enabled the rural youth to rundairy farm enterprise profitably. The study concluded that capacity building of rural youth could play an important role inretaining rural youth in farming.